2015
DOI: 10.1021/acs.jafc.5b03489
|View full text |Cite|
|
Sign up to set email alerts
|

Olfactory Impact of Higher Alcohols on Red Wine Fruity Ester Aroma Expression in Model Solution

Abstract: This study focused on the impact of five higher alcohols on the perception of fruity aroma in red wines. Various aromatic reconstitutions were prepared, consisting of 13 ethyl esters and acetates and 5 higher alcohols, all at the average concentrations found in red wine. These aromatic reconstitutions were prepared in several matrices. Sensory analysis revealed the interesting behavior of certain compounds among the five higher alcohols following their individual addition or omission. The "olfactory threshold"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 42 publications
6
97
0
Order By: Relevance
“…This decrease and increase of the fruity and spirit‐like aromas, respectively, are well in line with results derived from descriptive tasks, in which the concentration of the isobutanol/isoamyl alcohol vector was increased from 130 to 430 mg/L (de‐la‐Fuente‐Blanco et al ). The result is also in close agreement with the numerical results recently presented by Carmeleyre et al (). These authors observed by means of descriptive analysis that the addition of 131 mg/L of isobutanol and isoamyl alcohol (88 and 43 mg/L, respectively) to simple aroma mixtures of fruity esters and acetates generated a significant decrease in the intensity of fresh and jammy fruit attributes and increased the spirit‐like aroma intensity of the mixture.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This decrease and increase of the fruity and spirit‐like aromas, respectively, are well in line with results derived from descriptive tasks, in which the concentration of the isobutanol/isoamyl alcohol vector was increased from 130 to 430 mg/L (de‐la‐Fuente‐Blanco et al ). The result is also in close agreement with the numerical results recently presented by Carmeleyre et al (). These authors observed by means of descriptive analysis that the addition of 131 mg/L of isobutanol and isoamyl alcohol (88 and 43 mg/L, respectively) to simple aroma mixtures of fruity esters and acetates generated a significant decrease in the intensity of fresh and jammy fruit attributes and increased the spirit‐like aroma intensity of the mixture.…”
Section: Resultssupporting
confidence: 92%
“…This makes it an interesting and widely studied product in terms of aroma formation. Most studies have focused on binary interactions between relatively simple stimuli present in wine, such as those occurring between whisky lactone (woody aroma) and ethyl butyrate (fruity aroma) (Atanasova et al ,b) or among fruity esters and acetates involved in the perception of wine fruitiness ( Pineau et al , Lytra et al , , Carmeleyre et al ). Being a necessary starting point, those investigations ignored the effects of the numerous other stimuli present in the volatile fraction of wines.…”
Section: Introductionmentioning
confidence: 99%
“…Leucine/isoleucine was among the metabolites best able to distinguish the seeds and pulp of less from more advanced berries. Phenylalanine and leucine participate in the production of higher alcohols during fermentation, namely 2-phenylethanol and isoamyl alcohol, the most abundant higher alcohols found in wine; these higher alcohols affect the aromas of wine and model solutions (Yoshizawa et al, 1961; Äyräpää, 1967; Vilanova et al, 2013; Noguerol-Pato et al, 2014; Vidal et al, 2014; Cameleyre et al, 2015). Previous work has implicated 2-phenylethanol in Pinot noir aroma, the variety used in this study (Miranda-Lopez et al, 1992; Girard et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, co-fermentations produced higher content of higher alcohol, acetate and terpene, and lower content of volatile fatty acids with the exception of Sc-Td fermentation (Table 2). Higher alcohols contributed positively to the "fresh fruity", "vegetal" notes, and aroma complexity in young red wine [34]. Higher alcohols could react with organic acids to form esters with a pleasant flavor, while excessive levels (≥500 mg/L) may lead to unpleasant flavor in alcohol beverage [35].…”
Section: Volatile Aroma Compounds In Citrus Winesmentioning
confidence: 99%